Efectueaza
a) (2^{2017} + 2^{2016} + 2^{2015} )÷ (2^{2010} + 2^{2009} + 2^{2008} )
b) 2017^{2017} -2016* 2017^{2016} - 2016^{0} * 2017^{2016}
Răspunsuri la întrebare
Răspuns de
15
a)
[tex](2^{2017}+2^{2016}+2^{2015}):(2^{2010}+2^{2009}+2^{2008})=\\ =(2^{2015}\cdot2^2+2^{2015}\cdot2^1+2^{2015}):(2^{2008}\cdot2^2+2^{2008}\cdot2^1+2^{2008})=\\ =(2^{2015}(2^2+2^1+1)):(2^{2008}(2^2+2^1+1))=\\ =2^{2015}:2^{2008}=2^7=128[/tex]
b)
[tex]2017^{2017}-2016\cdot2017^{2016}-2016^0\cdot2017^{2016}=\\ =2017^{2016}\cdot2017^1-2017^{2016}\cdot2016-2017^{2016}=\\ =2017^{2016}(2017-2016-1)=0[/tex]
[tex](2^{2017}+2^{2016}+2^{2015}):(2^{2010}+2^{2009}+2^{2008})=\\ =(2^{2015}\cdot2^2+2^{2015}\cdot2^1+2^{2015}):(2^{2008}\cdot2^2+2^{2008}\cdot2^1+2^{2008})=\\ =(2^{2015}(2^2+2^1+1)):(2^{2008}(2^2+2^1+1))=\\ =2^{2015}:2^{2008}=2^7=128[/tex]
b)
[tex]2017^{2017}-2016\cdot2017^{2016}-2016^0\cdot2017^{2016}=\\ =2017^{2016}\cdot2017^1-2017^{2016}\cdot2016-2017^{2016}=\\ =2017^{2016}(2017-2016-1)=0[/tex]
arianaherta:
Mersi
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Istorie,
8 ani în urmă
Limba română,
9 ani în urmă
Limba rusă,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă